Analisis Potensi Event Pariwisata di Kabupaten PALI - Hasan, Hanif (Tourism, Hospitality And Culture Insights Journal, 2024)
This research analyzes the potential of tourism events in Kabupaten PALI, Sumatera Selatan, by focusing on three key locations: Candi Bumi Ayu, Dekranasda PALI, and Lapangan Gelora Pramuka. Utilizing the 4A approach (Attraction, Amenity, Accessibility, and Ancillary), the study identifies the strengths and areas for improvement in these venues to support tourism development. Findings highlight significant opportunities for cultural festivals, heritage exhibitions, and community events that can enhance local economic growth and tourism sustainability. Strengthened infrastructure, improved amenities, and coordinated event management are recommended to maximize the region’s tourism potential and attract domestic and international visitors.